Impact of information epidemic in the COVID-19 pandemic - Sharma, Raman; Kumar, Mahendra; Saini, Arti (International Journal Of Community Medicine And Public Health, 2024)
In December 2019, the first case of Corona virus was identified in Wuhan, China. On March 11th, 2020, the World Health Organization (WHO) declared COVID-19 a pandemic due to a rapid surge in case numbers. This global health crisis has been accompanied by a significant amount of misleading and false information about COVID-19, creating uncertainty among the public as they seek trustworthy and reliable sources. The impact of misinformation extends beyond information sharing it can fundamentally distort common public perceptions of the risks associated with the virus. The unregulated dissemination of both accurate and inaccurate information on social media further contributes to the confusion, transforming a pandemic into an infodemic.